No association between variation in the NR4A1 gene locus and metabolic traits in white subjects at increased risk for type 2 diabetes - Fritsche Andreas; Stefan Norbert; Claussen Claus D; Schick Fritz; Machann Jürgen; Machicao Fausto; Müssig Karsten; Häring Hans-Ulrich; Staiger Harald (BMC, 2010)
Abstract Background The nuclear receptor NR4A1 is implicated in metabolic regulation in insulin-sensitive tissues, such as liver, adipose tissue, and skeletal muscle. Functional loss of NR4A1 results in insulin resistance and enhanced intramuscular and hepatic lipid content. Therefore, we investigated in a cohort of white European subjects at increased risk for type 2 diabetes whether genetic variation within the NR4A1 gene locus contributes to prediabetic phenotypes, such as insulin resistance, ectopic fat distribution, or β-cell dysfunction. Methods We genotyped 1495 subjects (989 women, 506 men) for five single nucleotide polymorphisms (SNPs) tagging 100% of common variants (MAF = 0.05) within the NR4A1 gene locus with an r2 = 0.8. All subjects underwent an oral glucose tolerance test (OGTT), a subset additionally had a hyperinsulinemic-euglycemic clamp (n = 506). Ectopic hepatic (n = 296) and intramyocellular (n = 264) lipids were determined by magnetic resonance spectroscopy. Peak aerobic capacity, a surrogate parameter for oxidative capacity of skeletal muscle, was measured by an incremental exercise test on a motorized treadmill (n = 270). Results After appropriate adjustment and Bonferroni correction for multiple comparisons, none of the five SNPs was reliably associated with insulin sensitivity, ectopic fat distribution, peak aerobic capacity, or indices of insulin secretion (all p ≥ 0.05). Conclusions Our data suggest that common genetic variation within the NR4A1 gene locus may not play a major role in the development of prediabetic phenotypes in our white European population.